SCLEREDEMA DIABETICORUM; A RARE DISEASE - Amber Waqar; Saleh Khurshied; Mahvish Aftab Khan; Aisha Baloch; Mohammad Riaz Khan; Nawal Khurshid (Journal of Ayub Medical College Abbottabad, 2024)
Scleredema Diabeticorum (SD) is a rare condition characterized by diffuse, symmetrical induration along with non-pitted swelling mostly on the upper back as a result of mucin being deposited in the dermis. It can also involve posterior neck, shoulders, and scalp. We report a case of 48 years old female patient from Pakistan, with uncontrolled diabetes mellites type 2 for the last 15 years, presenting with thickened skin at the back of the neck resulting in difficulty in neck and shoulder movements. This led to decreased functional class from I to II causing her to develop insomnia and depression. Scleredema diabeticorum is a difficult disease to manage as it runs a long and debilitating course with little propensity of remission with available treatments.